Adherence to Recommended Post-Splenectomy Immunizations to Reduce the Risk of Sepsis: The University of Washington Experience. (September 2020) - Pozdeyev, Nikita; Patel, Arpit; Pottinger, Paul S.; Leu, Michael; Payne, Thomas H.
Immunizations against Streptococcus pneumoniae, Neisseria meningitidis, and Haemophilus influenzae type b are recommended for patients undergoing splenectomy to decrease the risk of developing overwhelming infections. The authors sought to determine adherence to these recommendations by providers at UW Medicine. Regional immunization records for patients who underwent splenectomy between October 2015 and January 2019 were analyzed to measure compliance with immunization guidelines from the US Centers for Disease Control and Prevention (CDC). Among 253 patients who underwent splenectomy, 38 (15%) received all 7 immunizations against S pneumoniae, N meningitidis, and H influenzae type b recommended by the CDC; 95% of patients received at least 1 pneumococcal vaccine; 26% percent of patients did not receive MenB-4C vaccine. Many patients (3% to 10%) received redundant immunizations not in accordance with CDC recommendations. Development of state and national immunization registries and systems to improve adherence with post-splenectomy immunization guidelines may reduce risk for life-threatening infections.